Urinary Level of Liver-Type Fatty Acid Binding Protein Reflects the Degree of Tubulointerstitial Damage in Polycystic Kidney Disease - Shiika Watanabe; Daisuke Ichikawa; Takeshi Sugaya; Keiichi Ohata; Kazuho Inoue; Seiko Hoshino; Kenjiro Kimura; Yugo Shibagaki; Atsuko Kamijo-Ikemori (Karger Publishers, 2018)
Background/Aims: Polycystic kidney disease (PKD) is a common, progressive, and heritable type of kidney disease. Although certain imaging modalities are useful for the diagnosis and staging of PKD, they cannot adequately monitor the severity of interstitial inflammation and fibrosis. Therefore, the present study evaluated the urinary level of liver-type fatty acid binding protein (L-FABP) as a marker of interstitial inflammation and fibrosis in PKD. Methods: Male PCK/CrljCrl-Pkhd1pck/Crl (PCK) rats (n = 34) were used as an animal model of the PKD. Age-and sex-matched Sprague-Dawley rats (SD) (n = 34) were used as controls. Urine samples were obtained from the rats at 8, 12, 16, 20, and 24 weeks of age, and the sera and kidney tissues were obtained at 8, 16, 20, and 24 weeks of age. Results: All PCK rats developed cysts, and the degrees of tubular epithelial cell proliferation and interstitial inflammation increased linearly with age in these model rats relative to the controls. Interstitial fibrosis tended to increase in the PCK rats from 8 to 20 weeks of age, and revealed a peak level at 20 weeks. The urinary L-FABP levels increased linearly with age in the PCK rats, and the levels at 12, 16, 20, and 24 weeks were significantly higher than those in the controls. The urinary levels of L-FABP in the PCK rats correlated significantly with the severity of tubulointerstitial damage; specifically, we observed a significant correlation of the urinary levels at 16 weeks of age with the total kidney volume at 20 weeks. In contrast, both PCK and SD rats exhibited similar serum levels of L-FABP. Conclusion: Urinary L-FABP reflects the progression of tubulointerstitial damage, and therefore, may be a useful marker for monitoring the progression of PKD.